Diseases of edible oilseed crops - Chattopadhyay, C., 1962- (CRC Press, an imprint of the Taylor and Francis Group, 2016)
"Diseases of Edible Oilseed Crops presents an unprecedentedly thorough collection of information on the diseases of cultivated annual oilseed crops, including peanut, rapeseed-mustard, sesame, soybean, sunflower, and safflower. Written by internationally recognized researchers, this book covers and integrates worldwide literature in the field up to 2014, setting it apart from other books that are only of regional importance. The book focuses on major diseases of economic importance to each crop. Each chapter is devoted to a type of crop and a profile of affecting diseases according to geographical occurrence, epidemiology, symptoms, causal pathogens, host-pathogen interactions, biotechnological aspects, and the latest approaches to understanding host-pathogen interactions. It also includes discussions on developments on controversial subjects in research in order to stimulate thinking and further conversation with an eye toward improvements and resolutions."--